2013
DOI: 10.3390/ijms14035036
|View full text |Cite
|
Sign up to set email alerts
|

Phospholipases of Mineralization Competent Cells and Matrix Vesicles: Roles in Physiological and Pathological Mineralizations

Abstract: The present review aims to systematically and critically analyze the current knowledge on phospholipases and their role in physiological and pathological mineralization undertaken by mineralization competent cells. Cellular lipid metabolism plays an important role in biological mineralization. The physiological mechanisms of mineralization are likely to take place in tissues other than in bones and teeth under specific pathological conditions. For instance, vascular calcification in arteries of patients with r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
48
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 57 publications
(48 citation statements)
references
References 657 publications
0
48
0
Order By: Relevance
“…They constitute the one of intercellular communication mechanisms, as it was shown in previous studies [5]. Moreover, numerous observations of Anderson [4, 612] and others revealed that similar submicron organelles may be also involved in the process of biomineralization [4, 612]. …”
Section: Introductionmentioning
confidence: 92%
“…They constitute the one of intercellular communication mechanisms, as it was shown in previous studies [5]. Moreover, numerous observations of Anderson [4, 612] and others revealed that similar submicron organelles may be also involved in the process of biomineralization [4, 612]. …”
Section: Introductionmentioning
confidence: 92%
“…Multiple PLA 2 isozymes are known to exist in vertebrates, including 31 different isoforms of PLA 2 in humans (28). PLA 2 preferentially acts on phospholipids (including phosphatidylcholine and phosphatidylethanolamine), with arachidonic acid present at the sn-2 position, and thus, the presence of arachidonic acid is an indicator of PLA 2 activity (28,29).…”
Section: Pla 2 and Enpp6 Expression And Activity In Mineralizing Cellsmentioning
confidence: 99%
“…Multiple PLA 2 isozymes are known to exist in vertebrates, including 31 different isoforms of PLA 2 in humans (28). PLA 2 preferentially acts on phospholipids (including phosphatidylcholine and phosphatidylethanolamine), with arachidonic acid present at the sn-2 position, and thus, the presence of arachidonic acid is an indicator of PLA 2 activity (28,29). The presence of PLA 2 isoforms has been confirmed in chondrocytes, osteoblasts, and cartilage, and these enzymes have also been localized to MVs and associated with matrix mineralization (28,30).…”
Section: Pla 2 and Enpp6 Expression And Activity In Mineralizing Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…1 The presence of different isoforms of phospholipase D (PLD) in chondrocytes 2-4 and in osteoblasts [5][6][7][8][9] were previously reported, suggesting that PLD may regulate differentiation, maturation, and function of cells. 1 The presence of different isoforms of phospholipase D (PLD) in chondrocytes 2-4 and in osteoblasts [5][6][7][8][9] were previously reported, suggesting that PLD may regulate differentiation, maturation, and function of cells.…”
Section: Introductionmentioning
confidence: 97%